2022
DOI: 10.1186/s13071-022-05183-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-malaria potency of wild and genetically modified Enterobacter cloacae expressing effector proteins in Anopheles stephensi

Abstract: Background Malaria is one of the most lethal infectious diseases in tropical and subtropical areas of the world. Paratransgenesis using symbiotic bacteria offers a sustainable and environmentally friendly strategy to combat this disease. In the study reported here, we evaluated the disruption of malaria transmission in the Anopheles stephensi-Plasmodium berghei assemblage using the wild-type (WT) and three modified strains of the insect gut bacterium, Enterobacter cloacae. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…Thus, the interaction between the gut microbiome of the sand fly host and the Leishmania parasites appears to be beneficial for the parasites. In addition, studies in mosquitoes showed that some gut bacterial species can directly or indirectly reduce [51][52][53][54][55][56][57], or enhance [58][59][60], parasite transmission. Conversely, pathogens such as the malaria parasite and Zika, and Chikungunya viruses can shape the abundance and composition of the mosquito gut microbiome [12,[61][62][63].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the interaction between the gut microbiome of the sand fly host and the Leishmania parasites appears to be beneficial for the parasites. In addition, studies in mosquitoes showed that some gut bacterial species can directly or indirectly reduce [51][52][53][54][55][56][57], or enhance [58][59][60], parasite transmission. Conversely, pathogens such as the malaria parasite and Zika, and Chikungunya viruses can shape the abundance and composition of the mosquito gut microbiome [12,[61][62][63].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…In addition to B. subtilis, we have isolated Asaia sp. and Enterobacter cloacae from the sand flies, both of which are known to be suitable paratransgenic agents, having previously been used to develop paratransgenic mosquitoes [57,[65][66][67].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Therefore, they probably play an essential role in sand fly vector competence for Leishmania parasites ( Louradour et al., 2017 ). Consequently, E. cloacae and B. subtilis can be considered as a shuttle system to deliver, express and spread foreign inserts to be used as promising candidates for the paratransgenic approach ( Hurwitz et al., 2011 ; Dehghan et al., 2017 ; Dehghan et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Achieving this step could prove complex due to various factors, including the bacteria's ability to persist and successfully establish colonies in the mosquito gut. As the parasite Plasmodium progresses within its invertebrate hosts (vectors), its quantity typically decreases, starting from 103-104 gametocytes and diminishing to 102-103 motile ookinetes, eventually reaching less than 5 oocysts [67]. Targeting and intervening at this bottleneck stage could be crucial in preventing parasite transmission.…”
Section: Resultsmentioning
confidence: 99%